CFD estimation of heat losses in thermal conductivity measurements - Adamczyk, Wojciech; Szelejewski, Filip; Kozołub, Paweł; Białecki, Ryszard; Kruczek, Tadeusz (Computer Assisted Methods in Engineering and Science; Vol 20 No 3 (2013), 2017)
Knowledge of a material thermal conductivity is essential in several engineering applications. This material property serves also as a measure of the quality of manufactured materials. Nowadays, a lot of effort is directed into development of non-destructive, fast and reliable measurement techniques. In the works of Adamczyk et al. [1] and Kruczek et al. [10], a new in situ conductivity measurement technique for an anisotropic material was developed. This method, due to its rapidity and nondestructive character, can be embedded in a manufacturing process. However, despite many advantages, the developed measuring technique has some drawbacks corresponding to the applied mathematical model, which is used for determining the material thermal conductivities. It neglects the effect of heat losses due to radiation and convection phenomena on the calculated values of thermal conductivities. In this work, the computational fluid dynamic (CFD) modeling was applied to estimate heat losses due to radiation and convection. The influence of omitting the radiative and convective heat transfer on the predicted temperature field and calculated thermal conductivities was investigated. Evaluated numerical results were compared against experimental data by using the developed in situ measurement technique for the thermal conductivity of anisotropic materials.